Psychometric properties of the Child Development Assessment Questionnaire (QAD-PIPAS) for use in population studies involving Brazilian children aged 0–59 months - Sonia I. Venancio (Elsevier, 2021)
Objective: To analyze the psychometric properties of the Child Development Assessment Questionnaire (QAD-PIPAS). Methods: This methodological study was comprised of two axes. The first one aimed to analyze the instrument's construct validity (discriminant and concurrent validity) and internal consistency, and the second one examined test-retest reliability, involving two different samples and procedures. For construct validity and internal consistency, the sample was recruited in Embu das Artes-SP, Brasilia-DF and Recife-PE during the immunization campaign in 2017, involving caregivers of 2005 children under 60 months of age (1295 under 36 and 710 from 37 to 59 months). For the test-retest analysis the sample consisted of 30 children aged 0–59 months old that attended daycare centers in Embu das Artes-SP in 2018. Results: Multivariate analyses of construct validity showed that the QAD-PIPAS was able to identify the association between the outcome (suspected child development delays) and expected risk and protective factors based on Nurturing Care Framework (OMS/UNICEF). A significant positive correlation was achieved between the scores of the QAD-PIPAS and CREDI in six of the eight age groups analyzed, with the most significant correlations being in the age groups from 25 to 30 and 31–36 months. Acceptable internal consistencies were identified in all age groups, with better performance above 36 months of age (Cronbach’s alpha between 0.61 to 0.80). We also found an adequate test-retest reliability (global Kappa 0.81). Conclusion: The QAD-PIPAS showed evidence of construct validity and reliability to be used in population studies involving children aged 0–59 months during multi-vaccination campaigns in Brazil.